ENPEP as a potential predictor of immune checkpoint inhibitor efficacy. (3rd December 2021) - Wang, Aoyun; Chu, Han; Jin, Zheng; Gong, Zhihua; Jia, Qingzhu; Zhu, Bo
Abstract: Background: The gene ENPEP encodes glutamyl aminopeptidase, which can cut N‐terminal aspartic acid from angiotensin II, and is related to tumorigenesis and immune microenvironment, however, the association between the expression of ENPEP and benefits of immune checkpoint inhibitors (ICIs) has had no investigation. Methods: We assess the immunotherapeutic predictive performance of ENPEP expression and mutation in multiple cohorts, including one discovery cohort (Pender cohort), four validation cohorts (Hugo cohort; Liu cohort; Mariathasan cohort; Zhao cohort), and one mutation cohort (Miao cohort). Cohorts from The Cancer Genome Atlas (TCGA) were used to explore mechanism and analysis prognosis. Results: In the discovery cohort, patients with lower ENPEP expression had superior response rates (47.2% vs. 36.1%) and over‐all survival (OS) (HR [95% CI] = 0.61 [0.39–0.96]; p = 0.032) compared with those with higher ENPEP expression. The association between ENPEP and immunotherapy efficacy was consistently observed in validation cohorts (Hugo: OS HR [95% CI] = 0.41 [0.11–1.45], p = 0.158; Liu: OS HR [95% CI] = 0.73 [0.44–1.20], p = 0.211; Mariathasan: OS HR [95% CI] = 0.84 [0.65–1.09], p = 0.181; Zhao: OS HR [95% CI] = 0.20 [0.04–1.01], p = 0.033; Pooled cohort: OS HR [95% CI] = 0.76 [0.61–0.95], p = 0.015), and in the mutation cohort (ENPEP mutation vs. wild type (WT), OS HR [95% CI] = 0.46 [0.26–0.93], p = 0.017). Reliably, ENPEP is associated with M2 macrophage infiltration and activation in TCGA. Conclusions: Our results demonstrated ENPEP is a potential biomarker to classify patients' response to ICIs treatment. Abstract : This study examines the effects the expression of the gene ENPEP may have on predicting performance of immune checkpoint inhibitors in treating various types of cancers. We have found that lower expression of ENPEP leads to a significantly greater response to immune checkpoint inhibitor, along with better overall survival. Thus, we propose ENPEP as a novel biomarker for predicting patients' response to immune checkpoint inhibitors.